Use of flow cytometry for pathogen detection (Project Spring) - Garrett, Trevor. (2009)
Outbreaks of waterborne diseases are usually caused by pathogenic bacteria and viruses, most of which are difficult to detect and quantify in water supplies and natural aquatic environments. The conventional practice is to enumerate indicator microorganisms as proxies for pathogens associated with faecal contamination. In the past, the commonly used indicators include total coliforms, faecal coliforms (FC) and faecal streptococci (FS). In recent years, the determination of specific indicator bacteria, such as Escherichia coli (FC) and Enterococci (FS), is slowly replacing these measurements, depending on the applications of the water (Mugglestone et al., 2001). In either case, the methods used typically entail plate incubations over a period of at least 24 hours and enumeration of colonies by microscopy. The disadvantages of such methods are the long analysis time involved and the non-culturability of some target bacteria. In addition, recent studies have shown that even in the absence of indicator bacteria, pathogenic viruses may still be present in water supplies (Grabow et al., 2001). These difficulties point to an urgent need to develop faster, more accurate methodologies for detecting target microbes.